Seasonal differences in the response of the high-latitude electron density to solar wind variability in time-scales of days and weeks - Borries, Claudia; Davis, Fredy; Iochem, Pelin; Tasnim, Samira; Vogt, Joachim (2023)
The solar wind impact is expected to cause a regular every day variability of the polar ionosphere. The objective of this presentation is to characterize the ionosphere response to solar wind variability in high-latitudes in time scales of days and weeks. Therefore, we are investigating how the solar wind variability is reflected in the ionosphere variability at Tromso, which is located in Scandinavia at 70°N, 19°E. The solar wind merging electric field is used to approximate the solar wind energy input into the geosystem. It can be shown that on timescales of days and weeks, the magnitude of correlation between TEC and merging electric field reaches similar values to the correlation of TEC and F10.7. However, the results show that the correlation between TEC and solar wind parameters depends strongly on local time, season and solar cycle. There is a clear annual cycle in the variability of the correlation coefficient, with higher correlation values in winter than in summer. The positive correlation in winter close to local midnight hours is considered to be related to precipitation effects increasing the electron densities. During summer in solar maximum condition, clear negative correlation values are retrieved. These are considered to be caused by increased convection and composition changes.